2010
DOI: 10.1016/j.foreco.2010.09.037
|View full text |Cite
|
Sign up to set email alerts
|

Phosphorus release from forest harvesting on an upland blanket peat catchment

Abstract: 1The aim of this study was to investigate the release of phosphorus (P) to receiving waters resulting 2 from harvesting 34-year-old lodgepole pine trees in an upland peat catchment. The study site was 3 within a 25.3-hectare (ha) area, and was drained by a stream that received flows from ploughed 4 furrows, mainly, via collector drains, and discharged directly to the salmonid Shrahrevagh River,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
38
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 58 publications
(46 citation statements)
references
References 31 publications
(36 reference statements)
7
38
1
Order By: Relevance
“…Dissolved reactive phosphorus leaching from degrading brash material to the underlying soil has been measured in many studies (Stevens et al, 1995;Väänänen et al, 2007;Rodgers et al, 2010;Finnegan et al, 2012). On the same study site, Finnegan et al (2012) found that DRP concentrations 13 were significantly higher under 5 year-old brash mats in the RB than in the adjacent SF,…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…Dissolved reactive phosphorus leaching from degrading brash material to the underlying soil has been measured in many studies (Stevens et al, 1995;Väänänen et al, 2007;Rodgers et al, 2010;Finnegan et al, 2012). On the same study site, Finnegan et al (2012) found that DRP concentrations 13 were significantly higher under 5 year-old brash mats in the RB than in the adjacent SF,…”
Section: Discussionmentioning
confidence: 95%
“…When the trees were planted, the land was double mouldboard ploughed, creating furrows and ribbons at 2 m spacing, which are perpendicular to the third-order stream. There is a moderate climate, which is heavily influenced by the proximity of the Atlantic Ocean, with average air temperatures of 13 °C in summer and 4 °C in winter, and a mean annual rainfall of 2000 mm (Rodgers et al, 2010). Blanket peat of varying depth (minimum depth measured, 1 m) down to 2 m covers all areas.…”
Section: Study Site Description and Managementmentioning
confidence: 99%
“…Harvesting appropriately sized coupes in a catchment at any one time can minimise the nutrient concentrations in the main rivers (Rodgers et al 2010). In their study, Cummins and Farrell (2003) found that the study streams had P concentrations well above critical levels for eutrophication, but they didn't know what implications these pollutions had for downstream river-water quality in larger channels.…”
Section: P Concentrations In Downstream Rivermentioning
confidence: 95%
“…afforestation have been associated with environmental costs, ranging from acidification (Allott et al, 1990(Allott et al, , 1997Kelly-Quinn et al, 1996Cruikshanks et al, 2008;Feeley et al, 2011), sediment release (Rodgers et al, 2010), nutrient enrichment (Rodgers et al, 2010;Drinan et al, 2013a) to hydrological changes (Drinan et al, 2013b). For example, many studies have highlighted the exacerbating effect of forestry on water draining forested peatlands (Allott et al, 1990(Allott et al, , 1997Dalton, 2000) and episodic acidifying events (Kowalik et al, 2007;Evans et al, 2008;Ormerod and Durance, 2009;O'Dwyer and Taylor, 2010;Feeley et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…In addition, particulate forms of phosphorus (P), nitrogen (N) and carbon (C) are carried along with eroded material causing enrichment effects in receiving waters. The sources of nutrients under such circumstances may be anthropogenic fertilisation of commercial forestry or agricultural lands (P and N), forest harvest operations, or peat degradation leading to erosion of the terrestrial C pool (Cummins and Farrell, 2003;Rodgers et al, 2010;Drinan et al, 2013b) with aquatic impacts extending downstream.…”
Section: Introductionmentioning
confidence: 99%